2000
DOI: 10.1212/wnl.54.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of cognitive development

Abstract: In a test of verbal fluency, children tended to activate cortex more widely than adults, but activation patterns for fluency appear to be established by middle childhood. Thus, functional MRI using verbal fluency paradigms may be applied to pediatric patient populations for determining language dominance in anterior brain regions. The greater activation found in children, including the right inferior frontal gyrus, may reflect developmental plasticity for the ongoing organization of neural networks, which unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
233
5
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(271 citation statements)
references
References 33 publications
23
233
5
9
Order By: Relevance
“…Consistent with reports in the literature for children and adult subjects [30][31][32], fMRI expressive language tasks produced reliable activation of left frontal language areas in this cohort of healthy teenagers. Our finding that fMRI results were observable for every subject while MEG activations were less pronounced is consistent with another study comparing fMRI and MEG in adults during a naming task [33].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with reports in the literature for children and adult subjects [30][31][32], fMRI expressive language tasks produced reliable activation of left frontal language areas in this cohort of healthy teenagers. Our finding that fMRI results were observable for every subject while MEG activations were less pronounced is consistent with another study comparing fMRI and MEG in adults during a naming task [33].…”
Section: Discussionsupporting
confidence: 90%
“…Letter fluency is an executive function task mediated by cortical and subcortical brain structures in healthy individuals. Functional imaging studies of verbal fluency have reported left inferior frontal and dorsolateral prefrontal activation (Abrahams et al, 2003;Fu et al, 2002;Gaillard et al, 2000;Gourovitch et al, 2000;Paulesu et al, 1997;Phelps et al, 1997) and right cerebellar activation (Fu et al, 2002;Hubrich-Ungureanu et al, 2002;Weiss et al, 2003). In addition, lesion studies support the role of the frontal lobes (e.g., Baldo et al, 2001) and cerbellum in executive function tasks (Akshoomoff et al, 1992;Levisohn et al, 2000;Paradiso et al, 1997;Riva and Giorgi, 2000;Schmahmann and Sherman, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…The letter fluency task relies on basic word knowledge and initiation of efficient lexical retrieval strategies to name appropriate items whereas the category fluency task depends to a greater extent on overlearned semantic knowledge. Both tasks are mediated by left prefrontal cortex in most typically developing individuals (Abrahams et al, 2003;Fu et al, 2002;Gaillard et al, 2000;Gourovitch et al, 2000;Paulesu et al, 1997;Phelps et al, 1997;Szaflarski et al, 2002). Individuals with ASD show impairments on behavioral measure of the letter fluency task relative to typically developing controls (Rumsey and Hamburger, 1988;Rumsey and Hamburger, 1990;Turner, 1999, but see Minshew et al, 1997 adults with severe dyslexia (Rumsey and Hamburger, 1990) and clinical norms (Kleinhans et al, 2005).…”
Section: Introductionmentioning
confidence: 99%